Diversity and Community Assemblage of Littoral Zone Benthic Macroinvertebrates in Jagadishpur Reservoir - Shah, Deep N; Shah, Ram D Tachamo; Pradhan, Bandana K (Nepal Journal of Science and Technology, 2012)
Littoral benthic macroinvertebrates diversity and community assemblage of Jagadishpur Reservoir were studied during post-monsoon (2008) and pre-monsoon (2009) seasons. Altogether twelve sites in the littoral zone of the reservoir were sampled for benthic macroinvertebrates by using a kick-and-sweep method with a standard handnet. At each site, benthic macroinvertebrate samples were taken from different possible substrate types. The environmental variables of each site were collected based on Lentic Ecosystem Field Protocol during sampling. Biological metrics were used to describe the diversity and composition of benthic macroinvertebrates. The relationship between benthic macroinvertebrates assemblage and substrate types were examined by using principal component analysis. Cluster analyses were performed to describe the similarity among samples. In total, 50 taxa, belonging to 15 orders were recorded for littoral zone of the reservoir. The recorded higher number of taxa (family level) belonged to order Heteroptera (water bugs) and Diptera (flies), and class Mollusca. Mollusca for post-monsoon and Diptera (particularly Chironomidae) for pre-monsoon shared the highest proportion in the total density. Shannon diversity index (H’) for post-monsoon was 1.82±0.46 and for pre-monsoon was 1.38±0.53 and was significantly different between seasons (p=0.01). Principal component analysis revealed that increase in taxa numbers were positively correlated to soft substrates while negatively correlated to non-soft substrates in littoral zone of the reservoir. Cluster analyses discriminated the sites into two main groups for both seasons. The study concludes that benthic macroinvertebrates diversity is highly influenced by substrate types, water level fluctuation, and human accessibility to the reservoir. Therefore, in order to stabilize benthic macroinvertebrates diversity and their abundance, it is essential to maintain surface water level, stabilize bank substrate and minimize human pressure. DOI: http://dx.doi.org/10.3126/njst.v12i0.6505 Nepal Journal of Science and Technology 12 (2011) 211-19